Registration of NE Trailblazer C‐1, NE Trailblazer C0, NE Trailblazer C2, NE Trailblazer C3, NE Trailblazer C4, and NE Trailblazer C5 Switchgrass Germplasms. Issue 2 (15th April 2016) - Vogel, Kenneth P.; Mitchell, Robert B.; Sarath, Gautam
Abstract : NE Trailblazer C‐1 (GP‐101, PI 672015), NE Trailblazer C0 (GP‐100, PI 672014), NE Trailblazer C2 (GP‐102, PI 672016), NE Trailblazer C3 (GP‐103, PI 672017), NE Trailblazer C4 (GP‐104, PI 672018), and NE Trailblazer C5 (GP‐105, PI 672019) switchgrass ( Panicum virgatum L.) germplasms were released by the USDA‐ARS and the University of Nebraska‐Lincoln on 10 Sept. 2014. These germplasms were developed by six generations of divergent breeding for in vitro dry matter digestibility (IVDMD). As a result of the multigenerations of recurrent breeding, the resulting populations differ significantly for IVDMD and for 25 other forage quality or biomass composition traits, including both acid detergent and Klason lignin. Plants in the high IVDMD populations also had altered anatomical structure. The lignin concentration of the stems was altered more than that of the leaves. The germplasm populations also differ significantly for winter survival. Altering plant composition by selection for IVDMD adversely affected the winter survival fitness of the resulting populations by unknown mechanisms. Plants from these germplasms can be used in genetics studies for determining the inheritance of multiple biomass composition traits and for identifying genes controlling specific biomass composition properties and winter survival of switchgrass and other perennial grasses.